2021
DOI: 10.1186/s12991-021-00344-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress during the COVID-19 pandemic in Ethiopia: an online cross-sectional study to identify the need for equal attention of intervention

Abstract: Background The COVID-19 pandemic led individuals to suffer from different levels of mental health problems such as psychological distress, anxiety, depression, denial, panic, and fear. This study aimed at determining the prevalence of psychological distress and associated factors among the Ethiopian population during the COVID-19 pandemic. Methods A cross-sectional study was performed through an online survey using different online platforms. The q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 23 publications
4
53
0
Order By: Relevance
“…Healthcare workers face several challenges in treating patients with COVID-19: reducing the spread of infection; developing suitable short-term strategies; and formulating long-term plans. 13 The overall prevalence of psychological distress among healthcare workers in this study was 28.9% which underscores the grave situation that more than one in four healthcare workers have psychological distress. This finding was similar to the study conducted in Ethiopia (25.5%).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Healthcare workers face several challenges in treating patients with COVID-19: reducing the spread of infection; developing suitable short-term strategies; and formulating long-term plans. 13 The overall prevalence of psychological distress among healthcare workers in this study was 28.9% which underscores the grave situation that more than one in four healthcare workers have psychological distress. This finding was similar to the study conducted in Ethiopia (25.5%).…”
Section: Discussionmentioning
confidence: 53%
“…A low score indicates low levels of psychological distress and high scores indicate high levels of psychological distress. The final scores were categorized into four levels: "Likely to be well (10)(11)(12)(13)(14)(15)(16)(17)(18)(19))", "Likely to have the mild disorder (20-24)", Likely to have a moderate disorder (25-29), Likely to have a severe disorder (30-50). For further analytical purpose, "likely to have a mild disorder," "Likely to have a moderate disorder," "Likely to have severe disorder" were grouped as "Likely to have psychological distress' whereas "likely to be well" was categorized as "No psychological distress".…”
Section: Data Collection Tools and Techniquesmentioning
confidence: 99%
“…Residing in Victoria was chosen as a predictor since the state of Victoria (compared to other Australian states) has experienced one of the strictest lockdowns in the world and we wanted to investigate whether such drastic measures (compared to more lenient guidelines) would contribute to higher levels of mental distress. Further, COVID-19 studies have demonstrated that older adults are less negatively affected in terms of mental health outcomes compared to younger adults (e.g., [ 6 , 7 , 77 ]) but it is unclear if this relationship exists in parents. In addition, past research demonstrated that higher epidemic risk perception was associated with higher distress (e.g., [ 61 , 63 ]) but the data for parents and those with chronic illness are largely lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The unpredictable nature of the 2019-2020 Coronavirus pandemic has been shown to substantially increase the reported mental health disorders [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of COVID-19 on mental health disorders has been demonstrated in large and worldwide cohort studies. The initial reports of the outbreak in the news and the social media platforms lead to a disturbing increase in anxiety due to psychological and physical stressors, fear of contracting the disease, concerns for financial consequences, life routine disruption, and more [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%